INTERNATIONALIZATION OF SUPPLY CHAINS OF DOMESTIC AGRICULTURAL PRODUCTS IN A TURBULENT ENVIRONMENT - SADOVNYK, Oleksandr; IVASHCHENKO, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The essence of internationalization as a process of expanding economic activity and a strategic response to domestic market restrictions, threats of political or economic destabilization, changes in consumer demand and logistical challenges is considered. The primary sources of development of internationalization of supply chains are given, which include transnational corporations, which include enterprises located in two or more countries, are interconnected by ownership relations and have a significant impact on the development of industry relations. It is established that since the beginning of the Russian war against Ukraine, the supply chains of domestic agricultural products have experienced significant logistical obstacles, which materialized in the form of blocking of major seaports, overloading of alternative corridors, an increase in logistics costs compared to the pre-war level, insufficient capacity of border infrastructure and restrictions on the transportation of certain goods in transit through individual countries. The directions for overcoming the vulnerability of agricultural markets and supply chains are considered, in particular, the development of new sustainable logistics routes, the internationalization of the activities of Ukrainian agricultural enterprises, the attraction of international partners and investments. Seven directions of internationalization response to reduce risks are proposed, in particular, diversification of sales markets, logistics diversification and construction of cross-border infrastructure, internationalization of strategic functions, participation in global production and sales networks, attraction of foreign partners and creation of joint ventures, digital internationalization and use of e-commerce platforms, institutional support and international cooperation.